(p)ppGpp and DksA play a crucial role in reducing the efficacy of β-lactam antibiotics by modulating bacterial membrane permeability - Meenal Chawla; Jyoti Verma; Shashi Kumari; Tushar Matta; Tarosi Senapati; Prabhakar Babele; Yashwant Kumar; Rupak K. Bhadra; Bhabatosh Das (Microbiology Spectrum)
ABSTRACT The key signaling molecules in the bacterial stress-sensing pathway, the alarmone (p)ppGpp and the transcription factor DksA, play a crucial role in bacterial survival during nutritional deprivation and exposure to xenobiotics by modulating cellular metabolic pathways. In Vibrio cholerae, (p)ppGpp metabolism is solely linked with the functions of three proteins: RelA, SpoT, and RelV. The effects of threshold or elevated concentrations of (p)ppGpp on cellular metabolites and proteins, both in the presence and absence of DksA, have not yet been comprehensively studied in V. cholerae or other bacteria. We engineered the genome of V. cholerae to develop DksA null mutants in the presence and absence of (p)ppGpp biosynthetic enzymes. We observed that the N16:ΔrelAΔrelVΔspoTΔdksA V. cholerae mutant, which lacks both (p)ppGpp and DksA, exhibits higher sensitivity to different ꞵ-lactam antibiotics compared with the wild-type (WT) strain. Our whole-cell metabolomic and proteome analysis revealed that the cell membrane and peptidoglycan biosynthesis pathways are significantly altered in the N16:ΔrelAΔrelVΔspoT, N16:ΔdksA, and N16:ΔrelAΔrelVΔspoTΔdksA V. cholerae strains. Furthermore, the mutant strains displayed enhanced inner and outer membrane permeabilities in comparison to the WT strains. These results correlate with V. cholerae’s tolerance and survival against β-lactam antibiotics and may inform the development of adjuvants that inhibit stringent response modulators.IMPORTANCEThe (p)ppGpp biosynthetic pathway is widely conserved in bacteria. Intracellular levels of (p)ppGpp and the transcription factor DksA play crucial roles in bacterial multiplication and viability in the presence of antibiotics and/or other xenobiotics. The present findings have shown that (p)ppGpp and DksA significantly reduce the efficacy of ꞵ-lactam and other antibiotics by modulating the availability of peptidoglycan and cell membrane-associated metabolites by reducing membrane permeability. Nevertheless, the whole-cell proteome analysis of N16:ΔrelAΔrelVΔspoT, N16:ΔdksA, and N16:ΔrelAΔrelVΔspoTΔdksA strains identified the biosynthetic pathways and associated enzymes that are directly modulated by the stringent response effector molecules. Thus, the (p)ppGpp metabolic pathways and DksA could be a potential target for increasing the efficacy of antibiotics and developing antibiotic adjuvants.